Oncologic Critical Care 2019
DOI: 10.1007/978-3-319-74588-6_125
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infections and Ventilator-Associated Pneumonia in Cancer Patients

Abstract: Nosocomial infections or healthcare-acquired infections are a common cause of increased morbidity and mortality among hospitalized patients. Cancer patients are at an increased

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 78 publications
0
12
0
1
Order By: Relevance
“…Among hospital-acquired infections, VAP is one of the serious health problems that result in a higher mortality and morbidity rate. 30 , 31 The findings of the present study showed that 62 (40.8%) had adequate knowledge regarding the VAP prevention guidelines. The overall mean score of knowledge level was 11.1 ± 2.4.…”
Section: Discussionmentioning
confidence: 50%
“…Among hospital-acquired infections, VAP is one of the serious health problems that result in a higher mortality and morbidity rate. 30 , 31 The findings of the present study showed that 62 (40.8%) had adequate knowledge regarding the VAP prevention guidelines. The overall mean score of knowledge level was 11.1 ± 2.4.…”
Section: Discussionmentioning
confidence: 50%
“…However, it is noteworthy that the extracted dye was found to be more susceptible to the Gram-negative bacterium P. aeruginosa, which is the most common nosocomial infection causing catheter-associated blood infections, ventilator-related pneumonia, and blood infections. 62 The obtained results are herein significant because Gram-negative bacteria have been developing resistance to conventional antibiotics all over the world. 63 The extracted plant dyes may exhibit a different mechanism to inhibit microbes when compared to those of the antibiotics and thus may have significant clinical value in treating drug resistant microbes.…”
Section: ■ Experimental Sectionmentioning
confidence: 91%
“…Other common risk factors that commonly contribute to the development of such infections are individual age, chronic diseases such as renal failure, malignant tumor, cancer 24 along with AIDS, low immune status, leukaemia, etc. In addition, therapeutic procedures, endoscopic examinations, ventilation, intubation, surgical procedures, and catheterizations are other causes of nosocomial infections.…”
Section: Causes Of Nosocomial Infectionsmentioning
confidence: 99%